Nanoparticles in the Water Cycle Properties, Analysis and Environmental Relevance - Frimmel, Fritz H.; Niessner, R. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
As nanotechnology enters everyday life, engineered nanoparticles (ENP) will find their way into nature, including surface and groundwater. Here, distinguished experts of water chemistry present dedicated methods for the analysis of nanoparticles in the aquatic environment, their distribution and fate. This includes the influence of complex matrices such as wastewater, brown water with natural organic matter (NOM), and high salt concentrations as well as available and future standardized methods. The background of geogenic, natural nanoparticles is considered in a discussion of known environmental effects, including strategies to test for potential effects on human and environmental health.